Analog input/output unit for PC computer - A, Gantumur; D, Tselmeg (Scientific transaction of the National University of Mongolia. Physics, 2022)
Analog input part is built around A/D converter ADC0809. The chip offers 8 bit resolution for conversion of analog voltages into digital representation, it takes approximatelly 100 microseconds to do a conversion. It's specified differential nonlinearity is below 1/2 LSB.